GAMBARAN HARGA DIRI REMAJA PUTRI YANG MELAKUKAN SEKS PRANIKAH - Karen Christy; Shanty Sudarji (Psibernetika, 2018)
Puberty is experienced in adolescence that causes physical and sexual maturity. Sexual hormones that have begun to work encourage adolescents to engage in sexual behavior. Women are referred to as the most disadvantaged if they have premarital sex without long-term commitment. And losing your virginity will affect your self-esteem such as feeling insecure, embarrassed, guilty, sinful, dirty, scared, worried, fear not accepted and humiliation and others will arise after having premarital sex. The purpose of this study is to get an overview and know how the self-esteem of teenage girls who have premarital sex. The research method used in this study is qualitative research with phenomenological approach and using interview and observation method to obtain research data. Respondents in this study were five teenage girls who had premarital sex. The results in this study showed that only one respondent fulfilled all aspects of self-esteem. Then, three respondents fulfilled the aspect of feeling of worth. Two respondents fulfilled the aspect of feeling of competence, and two respondents fulfilled the feelings of belonging. The existence of family factors that also affect the respondents to perform premarital sex behavior as well as the existence of environmental factors, personality factors and hormonal factors. Premarital sex performed by these five respondents can be a picture that premarital sex in teenagers is a natural thing to do with a partner as a form of peak of love by teenagers though not married. So that adolescents are expected to study sex education by attending seminars to find out the impacts if premarital sex. Keywords:  Self-esteem, Self-esteem in teenage girls, teenage girls, premarital sex